Estimation of brain natriuretic peptide values from N-terminal pro brain natriuretic peptide levels and other factors. (25th January 2023) - Kajikawa, Y; Ueda, A; Ikeda, M; Hirota, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Backgrounds: Both brain natriuretic peptide (BNP) and N-terminal proBNP (NT-pro BNP) are established biomarkers that are necessary in the diagnosis and management of heart failure (HF). Recently with the introduction of angiotensin receptor-neprilysin inhibitor in the treatment of HF, the course of HF is now assessed using NT-ProBNP levels1). However, it is difficult to infer BNP concentration from NT-proBNP levels for a physician who is familiar with BNP. Generally, simultaneous measurement of BNP and NT-proBNP is not permitted in medical insurance. Purpose: To estimate BNP concentration from NT-proBNP levels and other factors as an equivalent prognostic strength compared to the actual BNP concentration. Methods: From August 2021 to October 2021, we measured BNP and NT-proBNP levels of patients who were known or suspected to have HF (n=200). We created a formula for estimating BNP concentration from the data of NT-proBNP, age, body mass index (BMI), white cell counts, hemoglobin (Hb), estimated glemerular filtration rate) (eGFR) and C-reactive protein (CRP) using multivariate analysis. Results: Patients' background were as follows: age 66.4±23.6 years, male /female : 112/88, BMI: 23.1±5.2 kg/m2, Hb level: 12.3±2.2 g/dL, albmine level: 3.7±0.7 g/dL, eGFR level: 63.3±27.0 mL/min/1.73m², CRP level; 1.80±4.67 mg/dL, BNP level: 103.3±207.9 pg/mL, NT-proBNP level: 1, 505.1±3, 479.6 pg/mL (mean ± SD). There was a strong correlation between BNP concentration and NT-proBNP level when using actual measured values (r= 0.84) and when using log-transformed values (r=0.92) in these patients.Using multiple regression analysis, we created an equation that estimated LogBNP=-0.864+0.734×LogNT-proBNP+0.005×age-0.003×eGFR-0.009×BMI+0.016×CRP (R²=0.89). Conclusion: This equation will be useful, especially for a physician who is not familiar with NT-proBNP. Testing BNP concentrations were reliably estimated from an equation featuring NT-proBNP, eGFR, age, BMI and CRP2), 3), 4).